2012
DOI: 10.4141/cjas2011-127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of distillers’ dried grains with solubles from corn, wheat or a 50:50 corn:wheat blend on performance, carcass characteristics and serum sulphate levels of feedlot steers

Abstract: Amat, S., Hendrick, S., McAllister, T. A., Block, H. C. and McKinnon, J. J. 2012. Effects of distillers’ dried grains with solubles from corn, wheat or a 50:50 corn:wheat blend on performance, carcass characteristics and serum sulphate levels of feedlot steers. Can. J. Anim. Sci. 92: 343–351. Two trials were conducted to evaluate the effects of corn (CDDGS), wheat (WDDGS) or a 50:50 corn:wheat blend (BDDGS) dried distillers’ grains with solubles (DDGS) on performance (Trials 1 and 2), carcass traits (Trial 2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
7
1
Order By: Relevance
“…While by-products can be used to partially replace grain in finishing rations, previous research has focused on the use of specific by-products in isolation. Due to the unique composition of each by-product, single ingredient substitution strategies often lead to the overfeeding of some nutrients and less efficient feed utilization (Amat et al 2012;Yang et al 2012). Furthermore, applying single ingredient substitution strategies limit the use of some by-products for finishing cattle.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While by-products can be used to partially replace grain in finishing rations, previous research has focused on the use of specific by-products in isolation. Due to the unique composition of each by-product, single ingredient substitution strategies often lead to the overfeeding of some nutrients and less efficient feed utilization (Amat et al 2012;Yang et al 2012). Furthermore, applying single ingredient substitution strategies limit the use of some by-products for finishing cattle.…”
mentioning
confidence: 99%
“…Strategic blending of various by-products can be used to limit disadvantages associated with single by-product inclusion in the diet (Zenobi et al 2012), namely unbalanced ruminal and postruminal energy and protein supply as well as reducing the potential for over and underfeeding particular nutrients (Amat et al 2012;Yang et al 2012). However, even when several byproducts are combined in the diet, the reduced starch and greater structural carbohydrate content in most byproducts as compared with grains (Marx et al 2000;Mustafa et al 2000) may result in insufficient energy content in the diet for finishing cattle.…”
mentioning
confidence: 99%
“…As a consequence of increased grain prices, feedlot operators have been searching for viable alternatives to cereal grain as energy sources for finishing cattle. Studies evaluating the use of byproducts from the cereal grain, oilseed, and bioethanol industries for finishing cattle have demonstrated that comparable carcass quality and average daily gain (ADG) can be attained, relative to barley grain, although the inclusion rate of the byproducts in diets may affect performance (Pylot et al 2000;Amat et al 2012;Yang et al 2012). Most previous studies have investigated dietary byproduct inclusion in isolation rather than utilizing a combination of byproducts.…”
Section: Introductionmentioning
confidence: 99%
“…McKinnon and Walker [21] reported that growing steers fed wheat distiller grain at 25 or 50% of dietary dry mater gained faster and were more eicient than steers fed a barley grain diet. In contrast, no beneit was reported when wheat distiller grain was fed at level of 17% [24] or at levels up to 40% [14] in growing diets. It appeared that when the level of wheat distiller grain is too high, dietary protein level can be exceeded to the protein requirement by animal.…”
Section: Distiller Grain For Growing Catlementioning
confidence: 68%